Pension Funds and Capital Market Development : How Much Bang for the Buck? - Raddatz, Claudio (Washington, DC: World Bank, 2012)
This paper studies the relation between institutional investors and capital market development by analyzing unique data on monthly asset-level portfolio allocations of Chilean pension funds between 1995 and 2005. The results depict pension funds as large and important institutional investors that tend to hold a large amount of bank deposits, government paper, and short-term assets; buy and hold assets in their portfolios without actively trading them; hold similar portfolios at the asset-class level; simultaneously buy and sell similar assets; and follow momentum strategies when trading. Although pension funds may have contributed to the development of certain primary markets, these patterns do not seem fully consistent with the initial expectations that pension funds would be a dynamic force driving the overall development of capital markets. The results do not appear to be explained by regulatory restrictions. Instead, asset illiquidity and manger incentives might be behind the patterns illustrated in this paper.